Pengaruh Harga, Kualitas, Dan Merek Terhadap Permintaan Minyak Goreng Menurut Perspektif Ekonomi Islam (Studi Kasus Ibu-ibu Rumah Tangga Di Sei Kera Hilir I Kec. Medan Perjuangan) - Azahra, Alma; Rahma, Tri Indha Fadhila; Hasibuan, Reni Ria Armayani (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the price has a positive and significant effect on the demand for cooking oil products. Which means that if the price of an item increases, people will reduce the quantity of the item demanded. Vice versa, people will increase the quantity of goods demanded if the price decreases. Quality has a positive and significant effect on the demand for cooking oil products. Which means the quality of goods to be one of the factors that affect the amount of demand for goods. Goods with good quality will be easily accepted in the market so that the demand for these goods increases, while goods with poor quality are difficult to accept in the market and the number of requests for these goods tends to decrease. Consumers are more interested in goods with good quality, compared to poor quality. Brand has a partial and significant effect on the demand for cooking oil products. Which means if a product brand matches the tastes or habits of consumers, then the demand for a product brand will increase. Increased tastes, followed by product brand trends that follow tastes, will increase the demand for these goods. Price, quality, and brand have a simultaneous and significant effect on the demand for cooking oil products. This is evidenced by the Fcount value of (5.442) greater than Ftable (2.73) and a sig value of 0.038 <0.05.